KEEFEKTIFAN TEKNIK RESTRUKTURISASI KOGNITIF UNTUK MENINGKATKAN MOTIVASI BELAJAR DALAM KONSELING INDIVIDU - Indri Presia Widuri (Universitas Negeri Makassar, 2022)
The purpose of implementing this individual counseling is to find out the effectiveness of cognitive restructuring techniques to increase student learning motivation at SMP Negeri 3 Palu. The background of the problem encountered is a decrease in the learning motivation of students who are affected by negative thoughts that arise in them. The focus of this problem emphasizes the negative thoughts of students that arise and are then changed to positive thoughts. The step taken by the counselor is to use the Cognitive Restructuring Technique with the initial stages of identifying negative thoughts that arise and then training students in changing negative thoughts into positive thoughts.